What is the impact of the fluid challenge technique on diagnosis of fluid responsiveness? A systematic review and meta-analysis - Laura Toscani; Hollmann D. Aya; Dimitra Antonakaki; Davide Bastoni; Ximena Watson; Nish Arulkumaran; Andrew Rhodes; Maurizio Cecconi (Critical Care, 2017)
Abstract Background The fluid challenge is considered the gold standard for diagnosis of fluid responsiveness. The objective of this study was to describe the fluid challenge techniques reported in fluid responsiveness studies and to assess the difference in the proportion of ‘responders,’ (PR) depending on the type of fluid, volume, duration of infusion and timing of assessment. Methods Searches of MEDLINE and Embase were performed for studies using the fluid challenge as a test of cardiac preload with a description of the technique, a reported definition of fluid responsiveness and PR. The primary outcome was the mean PR, depending on volume of fluid, type of fluids, rate of infusion and time of assessment. Results A total of 85 studies (3601 patients) were included in the analysis. The PR were 54.4% (95% CI 46.9–62.7) where <500 ml was administered, 57.2% (95% CI 52.9–61.0) where 500 ml was administered and 60.5% (95% CI 35.9–79.2) where >500 ml was administered (p = 0.71). The PR was not affected by type of fluid. The PR was similar among patients administered a fluid challenge for <15 minutes (59.2%, 95% CI 54.2–64.1) and for 15–30 minutes (57.7%, 95% CI 52.4–62.4, p = 1). Where the infusion time was ≥30 minutes, there was a lower PR of 49.9% (95% CI 45.6–54, p = 0.04). Response was assessed at the end of fluid challenge, between 1 and 10 minutes, and >10 minutes after the fluid challenge. The proportions of responders were 53.9%, 57.7% and 52.3%, respectively (p = 0.47). Conclusions The PR decreases with a long infusion time. A standard technique for fluid challenge is desirable.